2011
DOI: 10.1039/c1nr10617a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of double-stranded DNA to graphene oxide preventing enzymatic digestion

Abstract: Investigation into the interactions between graphene oxide (GO) and biomolecules is very important for broad applications of GO in bioassay and bioanalysis. In this work, we describe the interactions between double-stranded DNA (dsDNA) and GO. We demonstrated that dsDNA can bind to GO forming complexes (dsDNA/GO) in the presence of certain salts, which protects dsDNA from being enzymatically digested. On the other hand, we found that a nonionic surfactant, such as triton X-100, can block the formation of dsDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 60 publications
(62 reference statements)
6
108
0
Order By: Relevance
“…However, this protective effect seems more controversial and subject to debate in the case of double stranded NA. Lei et al demonstrated that this protective effect was highly dependent on salt concentrations in the case of double stranded NA and that it could be reversed by the addition of an anionic surfactant such as triton X-100 23 . In addition, enzymatic digestion by DNAse I and EcoR I has been shown to occur even if double stranded DNA was partially adsorbed onto GO whereas resistance to degradation by Exo III was reported at the same time 21 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…However, this protective effect seems more controversial and subject to debate in the case of double stranded NA. Lei et al demonstrated that this protective effect was highly dependent on salt concentrations in the case of double stranded NA and that it could be reversed by the addition of an anionic surfactant such as triton X-100 23 . In addition, enzymatic digestion by DNAse I and EcoR I has been shown to occur even if double stranded DNA was partially adsorbed onto GO whereas resistance to degradation by Exo III was reported at the same time 21 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…7,8 It is now generally accepted that the in vitro cellular toxicity of graphene is closely related to its surface functionalization. Moreover, the reactive groups on graphene surface may facilitate conjugation with various systems, such as polymers, 9 biomolecules, 10 DNA, 11 protein, 12 quantum dots, 13 and others, imparting GO with multifunctionalities for diverse biological and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Researches about the effects of graphene sheets and/ or GO on macro-biomolecules, such as DNA molecules [16][17][18], gene [19], and enzymes [20], have caught great interests, where results have shown several potential applications in bioassay and bioanalysis.…”
Section: Biomolecular Interfacingmentioning
confidence: 99%
“…Since GO has a high affinity to ssDNA, it has been used as promising sequential delivery vehicle [22], geneprotecting [16], and transfection agent [23]. Y. Zhang et al have investigated the π-π interaction between dsDNA and GO in buffer with different metal ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation